Changes in the role of Pacific decadal oscillation on East Asian winter surface temperature - Doo Young Lee; Sang-Wook Yeh; Hyein Jeong; Hyo-Seok Park (Environmental Research Letters)
The complex interaction between the Pacific decadal oscillation (PDO) and East Asian winter temperatures remains unclear. This study reveals that since the early 2000s, East Asia has experienced a strengthening of Aleutian low (AL) and Siberian high (SH) during negative PDO phases, leading to an intensified East Asian winter monsoon (EAWM). The increased pressure gradient between the SH and the AL, driven by warming in the western Pacific associated with the negative PDO phase, has significantly contributed to a shift toward cooling in East Asia (105°–150° E, 20°–50° N) since the early 2000s. Observations and model simulations provide evidence that the enhanced tropical convection in the western Pacific under a negative PDO phase has intensified the atmospheric circulations associated with the EAWM since the early 2000s. Understanding these dynamics is crucial for improving winter temperature forecasts in East Asia.